Microstructural evolution of mechanically alloyed Mo–Si–B–Zr–Y powders. (April 2016) - Yang, Tao; Guo, Xiping; Luo, Yucheng
Abstract: Elemental powder mixtures with compositions of Mo–13.8Si, Mo–20B and Mo–12Si–10B–3Zr–0.3Y (at.%) were respectively milled in a high energy planetary ball mill at a speed of 500 rpm. Microstructural evolution of powder particles during milling processes was evaluated. The results show that B can hardly be dissolved into Mo under present milling conditions and the additions of B and Si both accelerate the refining rate of Mo crystallites. For Mo–12Si–10B–3Zr–0.3Y system, the morphology and internal structure of powder particles change significantly with milling time. After 40 h of milling, an almost strain-free super-saturated molybdenum solid solution with a grain size of about 6.5 nm forms. The grain refinement mechanism and dissolution kinetics of solute atoms are highlighted. Both thermodynamic calculation and experimental results reveal that for the present alloy composition it is more favorable to form solid solution than amorphous phase. Graphical abstract: Microstructural evolution of mechanically alloyed Mo–Si–B–Zr–Y powders is evaluated from the points of particle morphology and internal structure, phase constituent, gain size, microstrain, and dissolution of solute atoms. Highlights: Dissoltion of B in Mo under present condition can be negligible. Morphology and internal structure of powder particles change markedly with MA. After 40 h of milling, almost strain-free Moss with grain size of 6.5 nm forms. Mo lattice constant changes with the dissolution of Si and Zr atoms. Thermodynamic analysis shows preferred formation for Moss than amorphous phase.